Urinary bladder lesions of bovine enzootic hematuria in Argentina - Aguirre Castro, Laura Sabrina; Barbeito, Claudio Gustavo; Medina, Diego Martín Nicolás; Colque Caro, Luis Adrián; Micheloud, Juan Francisco (Elsevier, 2025)
Bovine enzootic hematuria (BEH) is characterized by chronic hematuria and neoplasms in the urinary bladder. From 2013 to 2016, 64 bovine urinary bladders were collected at a slaughterhouse in Rosario de Lerma, Salta, Argentina. The animals came from endemic areas where the infestation of ferns (Pteridium spp., Pteris spp.) in pastures is high. Histopathological and immunohistochemical analyses were performed. A significant increase in bladder thickness of positive cases compared to negative controls was observed (BEH+:7.5 ± 2 vs. BEH-: 3.9 ± 0.8). Samples were classified according to the severity of the thickening as normal, mildly, moderately, or severely thickened. Non-neoplastic lesions (epithelial, vascular, and inflammatory) and neoplasms of epithelial and vascular origin with varying degrees of severity were observed. Pancytokeratin AE1-AE3 and VEGF C1 antibodies were used to diagnose and confirm the origin of epithelial and vascular neoplastic cells. Proliferation indices were determined based on PCNA expression. Confirmation of the diagnosis of animals affected by this disease in the region. It was demonstrated that proliferative changes justified the thickening of the urinary bladders and may be related to the future development of certain lesions. Even though, this finding is important in the early stages of the disease and can be used as a parameter for monitoring the disease. Lesions observed in BEH are remarkable and demonstrate the complexity of the interactions in bladder tissue during carcinogenesis. The development of lesions serves as a valuable model for investigating neoplastic lesions in the bladder, with potential implications for human bladder cancer.